Evaluation of Safety and Efficacy of Traditional Cree Medicinal Plants - Cieniak, Carolina (Université d'Ottawa / University of Ottawa, 2014)
This thesis evaluated traditional medicines used by the Cree First Nation of Eeyou Istchee (James Bay Region, Quebec, Canada) for safety and efficacy in the context of Type 2 diabetes and Alzheimer’s disease. Drug metabolism and absorption were evaluated using whole cell in vitro models: human liver microsomes and Caco-2 permeability assays, respectively. It was found that the 17 medicinal plant extracts had an effect on the cytochrome P450-mediated metabolism of one co-administered conventional antidiabetic therapy, repaglinide, while having no effect on another, gliclazide. Furthermore, 11 of the extracts were tested for absorption and had no effect on either conventional therapy. One promising botanical, Sarracenia purpurea L. (Sarraceniaceae), was studied in detail. The phytochemistry of the traditional water preparation was compared to the more widely used ethanol extract. The concentrations of the 10 phenolic compounds present, as well as an active principle, the iridoid glycoside morroniside, were very similar between the two extracts, with generally slightly higher concentrations of phenolics in the ethanol extract as expected. However, two triterpenes, betulinic acid and ursolic acid, were 107 and 93 times more concentrated, respectively, in the ethanol extract compared to the water. Further analysis of safety of S. purpurea and morroniside was examined using Caco-2 cells, a model for first-pass metabolism, using 19K microarrays. Following 4- hour and/or 24-hour exposure to 100 μg/mL S. purpurea or 8.8 μg/mL morroniside, no transcript changes related to metabolism or drug transport were significantly altered, thus further supporting its role as a generally safe botanical. However, when S. purpurea was examined in an in vivo model of Alzheimer’s disease, the TgCRND8 (Tg) mice, it increased the frenetic behaviour observed in the Tg mice and further impaired learning and memory as examined by the Morris Water Maze. This impairment was associated with an increased level of the PC(O-16:0/2:0) lipid second messenger. Taken together, these results suggest both potential safety and limitations of using Cree traditional medicines when co-administered with pharmaceuticals. While in vitro studies also suggested potential safety of S. purpurea, it impaired Tg mice in vivo. Furthermore, Cree elders clearly understand the limitations to their traditional therapy as they warned us not to use this plant medicine in a “weakened state”.